ANALISIS EFEKTIVITAS DAN EFISIENSI PENGELOLAAN PERSEDIAAN TERHADAP SISTEM PENGENDALIAN INTERNAL PADA PT SII X ELECTRONICS BATAM - Saputra, Paskalis Roy; Tipa, Handra (SCIENTIA JOURNAL, 2019)
With a good and regular internal control system in managing supplies, the manage of company will get useful reports to improve effectiveness and efficiency in inventory management. This study aims to decide the effectiveness and efficiency of inventory management on the internal control system. The independent variables in this study are the effectiveness and efficiency of inventory management. For the dependent variable in the research is the internal control system. Data collection techniques used in this research study using primary data sources. Data sources in this study are primary data obtained through questionnaires to respondents. The number of samples was 92 respondents from 120 respondents. The analysis technique used is validity test, normality test, multicollinearity test, heteroscedasticity test, R2 Determination test, multiple regression, hypothesis testing using t statistics to test the partial regression coefficients and f statistics to test the significant of the influence together with the level of significance 5 %. The results of this study show that partly the effectiveness and efficiency of inventory management has a significant effect on the internal control system. And simultaneously the effectiveness and management of inventory has significant effect on the internal control system. The value of Adjusted R square shows that jointly the effectiveness and efficiency of inventory management contributes to the internal control system by 60.2% while the remaining 39.8% is influenced by other variables not included in this study.